Management of the Wheat Curl Mite and Wheat Streak Mosaic Virus With Insecticides on Spring and Winter Wheat - Murphy, Carmen Y.; Burrows, Mary E. (Frontiers in Plant Science, 2021)
The wheat curl mite (WCM, Aceria tosichella Keifer) is an eriophyid mite that causes damage to cereal crops in the Northern Great Plains by feeding damage and through the transmission of plant viruses, including Wheat streak mosaic virus. Insecticide treatments were evaluated in the greenhouse and field for efficacy at managing WCM on wheat. Treatments tested were carbamates, organophosphates, pyrethroids, a neonicotinoid seed treatment, mite growth inhibitors, and organic materials review institute (OMRI) approved biocontrols, soaps, and oils. Treatment with carbamates, organophosphates, and pyrethroids decreased WCM in greenhouse trials compared to untreated controls 14 days after infestation. The seed treatment, mite growth inhibitors and organic pesticides did not reduce WCM populations effectively and consistently. Timing of application was tested using sulfur solution as the experimental treatment. Treating plants with sulfur 7 days after mite infestation reduced mites compared to the untreated control. In contrast, prophylactically applied sulfur and sulfur applied 14 days post-mite application were not timely. When tested under field conditions with plots infested with viruliferous mites, there was no yield difference detected between untreated control plots and plots sprayed with insecticides. Select carbamates, organophosphates, and pyrethroids have potential for use in greenhouse mite management, when appropriate.